Biological Invasions in South Africa 2020
DOI: 10.1007/978-3-030-32394-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens of Vertebrate Animals as Invasive Species: Insights from South Africa

Abstract: The study of disease organisms as invasive alien species has not received a great deal of attention in the field of invasion science. Introduced pathogens can have profound effects on living organisms, the ecosystems that they inhabit, and the economies that the ecosystems support. In this chapter, we use case studies of introduced diseases of domestic and wild animals (canine rabies, bovine tuberculosis, and rinderpest) and humans (smallpox, measles and human immunodeficiency virus, HIV) to illustrate the kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…3-11) deals with the current situation. The first chapters focus on specific taxa-terrestrial plants (Richardson et al 2020b), aquatic plants (Hill et al 2020a), terrestrial vertebrates (Measey et al 2020a), terrestrial invertebrates (Janion-Scheepers and Griffiths 2020), and pathogens that affect mammals, including humans (van Helden et al 2020). The ecology of diseases, such as those covered by van Helden et al (2020), has not yet been integrated within the invasion science agenda in South Africa.…”
Section: Scope and Arrangement Of This Bookmentioning
confidence: 99%
“…3-11) deals with the current situation. The first chapters focus on specific taxa-terrestrial plants (Richardson et al 2020b), aquatic plants (Hill et al 2020a), terrestrial vertebrates (Measey et al 2020a), terrestrial invertebrates (Janion-Scheepers and Griffiths 2020), and pathogens that affect mammals, including humans (van Helden et al 2020). The ecology of diseases, such as those covered by van Helden et al (2020), has not yet been integrated within the invasion science agenda in South Africa.…”
Section: Scope and Arrangement Of This Bookmentioning
confidence: 99%
“…This virus laid waste to cattle and wildlife populations across southern and eastern Africa, with severe ecological and economic consequences. It is estimated that 2.5 million cattle died in South Africa alone, with up to 95% mortality in some districts (van Helden et al 2020). Bovine tuberculosis (caused by the alien bacterium Mycobacterium bovis, which was introduced with cattle from Europe) has infected many wild mammals, including herbivores and carnivores.…”
Section: Brief Synopsis Of the Prominent Impacts Of Invasive Alien Sp...mentioning
confidence: 99%
“…The long-term effects on wild mammal populations are not well understood, but in the case of threatened species such as lions (Panthera leo) the effects of the disease may be compounded by other threatening factors such as habitat loss, poaching and feline immunodeficiency virus. This could have devastating consequences for the survival of lions in the wild (van Helden et al 2020). In a more recent development, the polyphagous shothole borer (Euwallacea fornicatus) and its fungal symbiont (the pathogen Fusarium euwallaceae) are known to have infected and killed individuals of at least 80 tree species, 35 of them native species (Paap et al 2018; Department of Agriculture, Forestry and Fisheries 2020).…”
Section: Brief Synopsis Of the Prominent Impacts Of Invasive Alien Sp...mentioning
confidence: 99%
“…Painted Reed Frogs were detected in Villiersdorp, Western Cape in 1997 and in Cape Town in 2004 (Davies et al 2013). A subsequent genetic study showed that these animals consisted of individuals that were extending their range from the Eastern Cape, and translocated animals from Mpumalanga, with the first records around 1995 (Tolley et al 2008). Davies et al (2013) explained how Painted Reed Frogs have been able to overcome their historical range limits by using a combination of human-mediated jump dispersal and artificial impoundments.…”
Section: Hyperolius Marmoratus (Painted Reed Frog)mentioning
confidence: 99%
“…However, most recently, is the arrival of 'domestic exotics' (Guo and Ricklefs 2010), species that have part of their native and introduced range within South Africa. Studies to date (Telford et al 2019;Tolley et al 2008) suggest that all invasions originate from populations within the country.…”
Section: Future Perspectives For Invasive Vertebratesmentioning
confidence: 99%